2011
DOI: 10.1186/gb-2011-12-6-r53
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing on genome-wide scale reveals the unique composition and expression patterns of microRNAs in developing pollen of Oryza sativa

Abstract: BackgroundPollen development in flowering plants requires strict control of the gene expression program and genetic information stability by mechanisms possibly including the miRNA pathway. However, our understanding of the miRNA pathway in pollen development remains limited, and the dynamic profile of miRNAs in developing pollen is unknown.ResultsUsing next-generation sequencing technology, we pyrosequenced small RNA populations from rice uninucleate microspores to tricellular pollen and control sporophytic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
107
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 85 publications
(116 reference statements)
13
107
1
Order By: Relevance
“…In addition, we identified two cultivar-specific miRNAs (osa-miR531a/c and nov-miR039) that accumulated to more than 10 RPM in one cultivar and less than 1 RPM in the other cultivar; osa-miR531 and nov-miR039 were specifically expressed in Sasanishiki and Hitomebore, respectively (Table 3). It is noteworthy that seven osamiRNAs, out of the 13 differentially expressed and two cultivar-specific miRNAs, have previously been reported to be expressed in developing rice pollen (Wei et al, 2011). Thus, we considered that these 15 miRNAs were candidates for rice miRNAs related to cool tolerance in immature anthers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we identified two cultivar-specific miRNAs (osa-miR531a/c and nov-miR039) that accumulated to more than 10 RPM in one cultivar and less than 1 RPM in the other cultivar; osa-miR531 and nov-miR039 were specifically expressed in Sasanishiki and Hitomebore, respectively (Table 3). It is noteworthy that seven osamiRNAs, out of the 13 differentially expressed and two cultivar-specific miRNAs, have previously been reported to be expressed in developing rice pollen (Wei et al, 2011). Thus, we considered that these 15 miRNAs were candidates for rice miRNAs related to cool tolerance in immature anthers.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous papers have suggested a relationship between miRNA profiles and rice anther or pollen development (Wei et al, 2011;Peng et al, 2012;Yan et al, 2015), further investigation is needed to understand the complete picture of the molecular genetic system(s) active in this tissue, and in particular the role of miRNAs in developing rice anthers under cool stress. Here, we focused on miRNA accumulation in immature anthers of rice under cool stress related to cool-temperature injury at the booting stage, and compared the miRNA profiles between cool-sensitive Sasanishiki and cool-tolerant Hitomebore cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Wei et al conducted deep sequencing of rice on a genome-wide scale to explore the composition and expression patterns of miRNAs in developing pollen, including uninucleate microspores, bicellular and tricellular pollen, and sporophytic tissues, and 292 known miRNAs and 75 novel miRNAs were identified. Of the 292 known miRNAs, 103 were found in abundance in developing pollen, and more than half of the novel miRNAs displayed pollen-or stage-specific expression [36]. Their research revealed differences in the composition and expression profiles of miRNAs for developing pollen and sporophytes, which suggest the important roles of the miRNA pathway in pollen development.…”
Section: Diverse Mirnas Exist In Pollenmentioning
confidence: 99%
“…For example, miR157, miR171, miR172, and miR824 were identified in mature Arabidopsis pollen using 454 sequencing and a miRCURY array (Chambers and Shuai, 2009;Grant-Downton et al, 2009b). miR171a and miR398 have been detected in male loblolly pine (Pinus taeda) gametophytes and rice pollen, respectively, by microarray analysis (Wei et al, 2011;Quinn et al, 2014). miR172b expression has been detected in the flower buds of Brassica campestris (Jiang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has been made in pollen research by employing a variety of resources and novel techniques (Jiang et al, 2014), which have provided important information regarding the molecular mechanism of pollen development and the control of crop fertility. Recently, it has been demonstrated that miRNAs are differentially expressed during the various periods of pollen development, and play specific roles in regulatory function in model plants ( Le Trionnaire and Twell, 2010;Wei et al, 2011). For example, miRNAs have been shown to function in mature Arabidopsis pollen, together with some of the most important genes involved in the miRNA silencing pathway, such as DCL1, AGO1, and RDR6 (Grant-Downton et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%